LEVERAGE, PROFITABILITAS DAN UKURAN PERUSAHAAN PADA NILAI PERUSAHAAN - Tasum Tasum (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
With the growth of companies operating in the consumer goods industry sector and the importance of information for the public about company performance. This research aims to examine the influence of Leverage, Profitability and Company Size on the Value of Companies in the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange in 2019-2022 . The population in this research is all 30 companies in the Consumer Goods Industry Sector on the Indonesia Stock Exchange in the 2019-2022 period and a sample of 16 companies was obtained which was determined using the purposive sampling method, so that the unit of analysis in this research was 16 x 4 = 64 sample units. Companies that are members of the Consumer Goods Industry sector on the Indonesia Stock Exchange for the 2019-2022 period. The data collection method used in this research is secondary data obtained from www.idx.co.id. The data analysis technique used is multiple linear regression. Based on the analysis results, it shows that the leverage and profitability variables have an influence on company value. Meanwhile, the company size variable has no influence on company value